Effect of energy pooling collisions in formation of a cesium plasma by continuous wave resonance excitation - Mahmoud, M.A.; Gamal, Y.E.E. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The generation of plasma in cesium vapor excited by cw laser is investigated theoretically. We have developed a computational model which quantitatively explains the laser power dependences of electron energy distribution function (EEDF) and the level population densities which were created during the interaction. The energy spectra of the electrons emerging from the interaction show that the mechanisms by which electrons gain energy through the resonant system can significantly increase the density of the resonant plasma. The nonlinear behaviour of the ion current suggests that the plasma formation is initiated via collisional ionization and collisional excitation, such as associative ionization, Penning ionization, or photoionization as well as energy pooling collisions.The Cs – Cs atom collisions play important role in the formation of a highly Cs plasma with the use of a relatively low power laser to excite a resonance transition. A comparison between the behaviour of the calculated ion current as a function of a laser power is proved to be a reasonable agreement with that measured by Pappas et al. (Appl. Spectrosc. 54, 2000, p. 1245). The results may be useful in designing and developing cw metal vapor lasers.
Optica Applicata, Vol. 40, 2010, nr 1, s. 129-141
Keywords: optyka; laser; collisional ionization; energy pooling; plasma; cesium